Persepsi Mahasiswa sebagai Calon Guru Pendidikan Agama Islam (PAI) dalam Menghadapi Tantangan Era Digital (Studi Pada Mahasiswa Program Studi PAI UIN Sumatera Utara) - Arlina, Arlina; Nabila, Ridha; Anggraini, Nursela; Maulana, Aldikha Aditya; Rahmaini, Siti (Asatiza: Jurnal Pendidikan, 2023)
This research is intended to collect the student's perceptions as candidates for pai in the digital age. The focus of the study is student perceptions, challenges, and the role of pai student in the digital age. The research methods used are qualitative with a descriptive study approach. The techniques used to collect data are observation, interviews, and documentation. Next, to analyze the data using the miles and huberman techniques of data reduction, data presentation, and deduction. As a result of this study, being a pai teacher in the digital age has been difficult because it has to face challenges such as scientific development and a moral crisis. As for the efforts that can be made, students must be digital literacy, innovating varying methods and media, following the growth of curriculum, and preparing materials according to the original sources.